KARAKTERISASI BERBASIS MARKA MOLEKULER ITS2 TERHADAP SUB-SPESIES KOMPLEKS Anopheles vagus vagus DAN Anopheles vagus limosus - Kartika Senjarini; Lailly Nur Uswatul Hasanah; Miatin Alvin Septianasari; Muhammad Khalid Abdullah; Rike Oktarianti; Syubbanul Wathon (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
The presence of intraspecies variations of An. vagus later categorized as the subspecies of An. vagus vagus and An. vagus limosus, could be an obstacle to the identification process, which is an important step for malaria vector’s competence characterization. Based on morphological identification, those subspecies could be distinguished by the presences of pale scales in prehumeral and pale bands  in proboscis. The objective of this research was to compare subspecies complexes of An. vagus morphologically and molecularly using Internal Transcribed Spacer 2 (ITS2). Anopheles samples were collected from Bangsring, Banyuwangi. Their phylogenetic tree was constructed by using NJ method based on their ITS2 sequences. BLAST result showed that An. vagus vagus and An. vagus limosus were similar to An. vagus FJ654649.1 from East Java Indonesia and East Timor based on its 99% homology and their molecular distance. The Neighbour Joining (NJ) tree grouped those subspecies in one clade with a boostrap value of 82%. This subspeciation might be due to the different rates of evolution. ITS2 sequences of An. vagus vagus and An. vagus limosus were submitted to GenBank with the accession number of MW314227.1 and MW319822.1, respectively. Kemunculan variasi intraspesies An. vagus yang kemudian dikategorikan sebagai subspesies An. vagus vagus dan An. vagus limosus menjadi kendala dalam proses identifikasi yang merupakan langkah penting dalam menentukan kompetensi vektor malaria. Berdasarkan karakter morfologi, subspesies tersebut dibedakan dengan adanya sisik pucat pada bagian prehumeral dan pita pucat pada probosis. Penelitian ini bertujuan untuk membandingkan subspesies An. vagus secara morfologis dan molekuler menggunakan Internal Transcribed Spacer 2 (ITS2). Nyamuk Anopheles didapatkan dari Bangsring, Banyuwangi. Konstruksi pohon filogeni dilakukan berdasarkan sekuen ITS2 yang dianalisis menggunakan metode NJ. Hasil BLAST menunjukkan, ITS2 An. vagus vagus dan An. vagus limosus memiliki tingkat homologi 99% dan jarak evolusi molekuler terendah dengan An. vagus FJ654649.1 dari Jawa Timur Indonesia dan Timor Timur. Pohon NJ mengelompokkan subspesies tersebut dalam satu klade dengan nilai boostrap 82%. Hal ini dapat terjadi karena perbedaan kecepatan evolusi yang memungkinkan terjadinya subspesiasi. Urutan basa ITS2 dari An. vagus vagus dan An. vagus limosus telah didaftarkan ke GenBank dengan nomor aksesi MW314227.1 dan MW319822.1.